Influence of dietary protein levels and some cold pressed oil supplementations on productive and reproductive performance and egg quality of laying Japanese quail - EL-HINDAWY, MM; ALAGAWANY, M; MOHAMED, LA; SOOMRO, J; AYASAN, T (Journal of the Hellenic Veterinary Medical Society, 2021)
The present study was carried out to examine the effect of dietary protein levels (18, 20, and 22%) and addition of cold-pressed oils (no addition, 1 g thyme, 1 g oregano, and 0.5 g thyme + 0.5 g oregano /kg diet) on the productive and reproductive performance and egg quality of Japanese quail at the laying period. 324 mature ten-week-old Japanese quails (216 females and 108 males) were used. Quails were randomly distributed to 12 treatment groups, 27 in each group, with 3 replicates of 9 quails (6 females and 3 males) per group. Feed conversion ratio (FCR) significantly improved in the layers fed with the diets containing 20 or 22% CP in all experimental periods, except in 3- to 4-month-old birds. The diets supplemented with thyme only or interaction with oregano improved FCR significantly compared to the control or oregano -administered group in all experimental periods, except in 2- to 3-month-old birds. Dietary supplementation with thyme oil caused the egg number and egg mass to increase significantly in all experimental periods compared to the other dietary groups. Fertility percentages were significantly higher in the groups which had oregano than in the control group. Dietary supplementation with thyme oil significantly increased the egg number (P<0.05) and egg mass (P<0.01) in all experimental periods compared to other dietary groups. Fertility and hatchability percentages were not significantly affected due to varying dietary protein levels throughout the experiment. In conclusion, the quails fed with a diet containing 20 to 22% CP or supplemented with oregano or thyme oil exhibited an improved productive and reproductive performance without any detrimental impacts on the other parameters studied.